Factors associated with phenoconversion of idiopathic rapid eye movement sleep behavior disorder: a prospective study - Yuan Yuan; Yuan Li; Hui Zhang; Yajie Zang; Xiaonan Liu; Yue Hou; Shuqin Zhan; Yanning Cai; Wei Mao; Piu Chan (npj Parkinson's Disease)
Abstract This study explores the effect of risk factors on the progression of idiopathic rapid eye movement (REM) sleep behavior disorder (iRBD) to α-synucleinopathies in a Chinese cohort. Patients with iRBD were enrolled and assessed for environmental factors and lifestyle using standardized structured questionnaires at baseline. All patients were prospectively followed for phenoconversion monitoring. The cumulative incidence was estimated using survival analysis. Of 155 iRBD enrolled in the cohort, follow-up information was available in 141 patients. The phenoconversion rate was 16.3% after 3 years, 27.6% after 5 years, and 57.2% after 10 years. Eighteen participants converted within 3 years, 27 converted within 5 years, and 36 converted within 10 years. IRBD with positive family history of parkinsonism had an increased risk of being converted to α-synucleinopathies, while tea drinking was associated with a decreased phenoconversion risk. Our findings shed light on a potential application of tea drinking in modifying iRBD progression.